Contested Crossing of Missionary Borders: William Fetler and the Russian Missionary Society in the Netherlands, 1931-1936 - De Jager, Koos-Jan (Trajecta, 2017)
This article explores the dynamics of Dutch Protestantism in the interwar period, focusing on the case of the Latvian Baptist pastor William Fetler and his Russian Missionary Society. In 1931, Fetler started his campaign in the Netherlands. A broad coalition of religious elites from the established churches responded to his call to action and supported him in raising funds for Russian mission. Over time the actions of Fetler were accompanied by fierce debates surrounding his personality, theological position, and financial practices. Notwithstanding the fact that Fetler's opponents could not make substantial arguments against him, the debates continued until 1934. The debates in the Dutch press and the disagreement among the leading Dutch theologians disturbed the Dutch missionary public. The people who supported existing organisations for Russian missions were willing to support Fetler as well as his RMS, but they held back because of the open quarrels over Fetler's reliability. In 1934, the Dutch teacher Van Schaardenburgh argued that Fetler had started missionary activities within the Netherlands. Because of Fetler's Dutch revivalist movement, Grosheide decided to resign as chairman of the Committee of Reference for Fetler's action. Grosheide's resignation caused a collapse of support for Fetler in the Netherlands. Theological differences thus became highly problematic and caused Fetler's exit from the margins of Dutch Protestantism.